(untitled) (American Journal of Islam and Society, 1986)
Like all great religions, Islam perceives God as the ruison &re of all things? Moreover, as a comprehensive scheme, Islam seeks to mold every sphere of man’s life in accordance with the moral principles it propagates. The end of Islamic political thought thus is to materialize these principles. Because they are codified in a body of law, the Islamic polity may be referred to as a nomocracy, making Islamic political thought a legal enterprise. Moreover, unlike the Western tradition of political thought in which the discussion of the nature of the “state” plays a central role, the “state” as an artificial corporate entity distinct from the community does not exist in Islamic political thought, but the “state” in the sense of a system of governance is a given. The primary question for any Islamic political thinker does not pertain to the nature of the state, but rather to the leadership of the community, on the one hand, and the relationship of that community with other political communities on the other. The political history of Islam has witnessed a host of various ways by which the aforementioned concerns have been dealt with. Up to modem times and the emergence of a new breed of thinkers responding to the Western impact, who deserve a category of their own, Islamic political thought could be discerned from the works of the following four groups: the theologian jurisconsults (fuquha), the literalists or the authors of the mirrors of the princes (udaba), the historiadphilosophers (mu’arikhin), and the philosophers (falasifa) ...